The Southern Energy Corridor: Turkey's Role in European Energy Security - Yorucu, Vedat (Lecture Notes in Energy, 2018)
This book highlights the importance of Turkey in diversifying supplies in future European energy security, focusing in particular on the rapidly emerging southern energy corridor. Turkey, by its location, occupies a key role in this corridor, fed by hydrocarbon supplies from Russian, Caspian, east Mediterranean and Arab sources. The book examines Turkey's role as a transit country (in addition to its own growing domestic energy market) and it utilizes the latest evidence on the geopolitics of various pipelines which convergence on Turkey. The evidence, including maps, strongly favor Turkey as an energy hub within a regional energy model driven by rational behavior and market forces. The book recommends an increasing strategic energy cooperation between the EU and Turkey to maximize mutual interest.